Comparison of Vaisala radiosondes RS41 and RS92 launched over the oceans from the Arctic to the tropics - Y. Kawai; M. Katsumata; K. Oshima; M. E. Hori; J. Inoue (Atmospheric Measurement Techniques, 2017)
To assess the differences between the RS92 radiosonde and its improved counterpart, the Vaisala RS41-SGP radiosonde version with a pressure sensor, 36 twin-radiosonde launches were made over the Arctic Ocean, Bering Sea, western North Pacific Ocean, and the tropical Indian Ocean during two cruises of R/V Mirai in 2015. The biases, standard deviations, and root mean squares (rms's) of the differences between the RS41 and RS92 data over all flights and altitudes were smaller than the nominal combined uncertainties of the RS41, except that the rms of the differences of pressure above 100 exceeded 0.6 hPa. A comparison between daytime and nighttime flights in the tropics revealed that the pressure difference was systematically larger during the day than at night above an altitude of 4.5 km, suggesting that there was some effect of solar heating on the pressure measurements, but the exact reason is unclear. The agreement between the RS41 and RS92 temperature measurements was better than the combined uncertainties. However, there were some noteworthy discrepancies presumably caused by the <q>wet-bulbing</q> effect on the RS92 radiosonde and the stagnation of the balloon. Although the median of the relative humidity differences was only a little more than 2 % of the relative humidity at all altitudes, the relative humidity of the RS92 was much lower than that of the RS41 at altitudes of about 17 km in the tropics. This dry bias might have been caused by the incomplete solar radiation correction of the RS92, and a correction table for the daytime RS92 humidity was calculated. This study showed that the RS41 measurements were consistent with the specifications of the manufacturer in most cases over both the tropical and polar oceans. However, further studies on the causes of the discrepancies are needed.